PLANT MEDIATED SYNTHESIS OF SILVER NANOPARTICLES AND THEIR APPLICATIONS - KULKARNI A.P.,; SRIVASTAVA A.A,; ZUNJARRAO R.S., (International Journal of Pharma and Bio Sciences, 2012)
To meet the increasing demands for commercial nanoparticles new eco-friendly “green” methods of synthesis are being discovered. Plant mediated synthesis of nanoparticles offers single step, easy extracellular synthesis of nanoparticles. The biosynthesis of silver nanoparticles using Bryophytes as plant source is practiced previously. They are easy to harvest and easy to make an extract and therefore, can be used for green synthesis of nanoparticles. In this study, the plant extract was prepared in ethanol and treated with silver nitrate to obtain nanoparticles. The synthesis of nanoparticles was confirmed by change in colour from pale green to reddish brown. Further, a peak between 400nm to 440nm was obtained on UV-Vis spectrophotometer which confirmed the biosynthesis of silver nanoparticles. Presence of silver nanoparticles was observed after carrying out SE microscopy with EDS that gave a strong silver signal. Since the nanoparticles show antibacterial activity, their immobilization was also carried out.